Effect of induced pyrexia on the disposition kinetics of ciprofloxacin in dogs - Faqir Muhammad; Masood Akhtar; M. Irfan Anwar; M. Javed Arshed (Veterinary Research Communications, 2009)

Immune Deficits in Allogeneic Hematopoietic Stem Cell Transplant (HSCT) Recipients - Muhammad A. Mir; Minoo Battiwalla (Mycopathologia, 2009)

Chemical and biological characterization of siderophore produced by the marine-derived Aureobasidium pullulans HN6.2 and its antibacterial activity - Weilin Wang; Zhe Chi; Guanglei Liu; Muhammad Aslam Buzdar; Zhenming Chi; Qianqun Gu (BioMetals, 2009)

Phytoremediation of Heavy Metals: Physiological and Molecular Mechanisms - Ruqaya Jabeen; Altaf Ahmad; Muhammad Iqbal (The Botanical Review, 2009)

Development of microsatellite markers for Shorea platyclados (Dipterocarpaceae) - Chin Hong Ng; Soon Leong Lee; Kevin Kit Siong Ng; Norwati Muhammad; Chai Ting Lee (Conservation Genetics Resources, 2009)

Microemulsion System with Improved Loading of Piroxicam: A Study of Microstructure - Muhammad Faizan Nazar; Asad Muhammad Khan; Syed Sakhawat Shah (AAPS PharmSciTech, 2009)

Changes in means and extreme events of temperature and precipitation in the Asia‐Pacific Network region, 1955–2007 - Gwangyong Choi; Dean Collins; Guoyu Ren; Blair Trewin; Marina Baldi; Yoshikazu Fukuda; Muhammad Afzaal; Theeraluk Pianmana; Purevjav Gomboluudev; Pham Thi Thanh Huong; Norlisam Lias; Won‐Tae Kwon; et al. (International Journal of Climatology, 2009)
In this study, spatial and temporal patterns of changes in extreme events of temperature and precipitation at 143 weather stations in ten Asia‐Pacific Network (APN) countries and their associations with changes in climate means are examined for the 1955–2007 period. Averaged over the APN region, annual frequency of cool nights (days) has decreased by 6.4 days/decade (3.3 days/decade), whereas the frequency of warm nights (days) has increased by 5.4 days/decade (3.9 days/decade). The change rates in the annual frequency of warm nights (days) over the last 20 years (1988–2007) have exceeded those over the full 1955–2007 period by a factor of 1.8 (3.4). Seasonally, the frequencies of summer warm nights and days are changing more rapidly per unit change in mean temperatures than the corresponding frequencies for cool nights and days. However, normalization of the extreme and mean series shows that the rate of changes in extreme temperature events are generally less than that of mean temperatures, except for winter cold nights which are changing as rapidly as the winter mean minimum temperature. These results indicate that there have been seasonally and diurnally asymmetric changes in extreme temperature events relative to recent increases in temperature means in the APN region. There are no systematic, regional trends over the study period in total precipitation, or in the frequency and duration of extreme precipitation events. Statistically significant trends in extreme precipitation events are observed at fewer than 30% of all weather stations, with no spatially coherent pattern of change, whereas statistically significant changes in extreme temperature events have occurred at more than 70% of all weather stations, forming strongly coherent spatial patterns. Copyright © 2009 Royal Meteorological Society

Purification and characterization of a chitinase from Serratia proteamaculans - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (World Journal of Microbiology and Biotechnology, 2009)

Integrated management of Helicoverpa armigera in chickpea in rainfed areas of Punjab, Pakistan - Waqas Wakil; Muhammad Ashfaq; M. U. Ghazanfar; Muhammad Afzal; Tahira Riasat (Phytoparasitica, 2009)

Biological impact of harmaline, ricinine and their combined effects with Bacillus thuringiensis on Spodoptera exigua (Lepidoptera: Noctuidae) - Muhammad Rizwan-ul-Haq; Qiong Bo Hu; Mei Ying Hu; Qing Shen Lin; Wan Li Zhang (Journal of Pest Science, 2009)

Book review: Percolation Theory for Flow in Porous Media, by A Hunt (Springer, Berlin, 2005) - Muhammad Sahimi (Hydrogeology Journal, 2009)

Characterization and application of monoclonal antibodies to bovine viral diarrhea virus nonstructural protein 5A - Muhammad Atif Zahoor; Daisuke Yamane; Yassir Mahgoub Mohamed; Kyousuke Kobayashi; Kentaro Kato; Yukinobu Tohya; Hiroomi Akashi (Archives of Virology, 2009)

Bioremediation and Phytoremediation of Pesticides: Recent Advances - Sarfraz Hussain; Tariq Siddique; Muhammad Arshad; Muhammad Saleem (Critical Reviews in Environmental Science and Technology, 2009)

Gibberellin production by pure cultures of a new strain of Aspergillus fumigatus - Muhammad Hamayun; Sumera Afzal Khan; Mir Ajab Khan; Abdul Latif Khan; Sang-Mo Kang; Sang-Kuk Kim; Gil-Jae Joo; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Seroprevalence of Toxoplasma gondii in sheep and goats in Rahim Yar Khan (Punjab), Pakistan - M. Ramzan; M. Akhtar; F. Muhammad; I. Hussain; E. Hiszczyńska-Sawicka; A. U. Haq; M. S. Mahmood; M. A. Hafeez (Tropical Animal Health and Production, 2009)

Peste des petits ruminants virus (PPRV) infection; Its association with species, seasonal variations and geography - Muhammad Abubakar; Syed Muhammad Jamal; Muhammad Javed Arshed; Manzoor Hussain; Qurban Ali (Tropical Animal Health and Production, 2009)

Feed supplementation prevents post-conception decline in milk progesterone concentrations associated with production stress in dairy buffaloes (Bubalus bubalis) - Sarzamin Khan; Muhammad Subhan Qureshi; Nazir Ahmad; Muhammad Amjed; Muhammad Younas; Altafur Rahman (Tropical Animal Health and Production, 2009)

Prospectus of growing barley and mustard with saline groundwater irrigation in fine‐ and coarse‐textured soils of Cholistan desert - Muhammad Akram Kahlown; Muhammad Akram; Zamir Ahmed Soomro; W. D. Kemper (Irrigation and Drainage, 2009)
The groundwater in Pakistani sandy deserts is generally highly saline and not suitable for drinking. However, it can be utilized for growing beneficial salt‐tolerant plants. To explore the potential of desert land for farm production two crops of barley and mustard were cultivated on coarse‐ and fine‐textured soils with saline water irrigations in the Cholistan desert. The salinity (electrical conductivity, EC) of irrigation water was 6.2 dS m −1 . The barley and mustard crops were irrigated five and four times, respectively, including pre‐sowing irrigation. At the end of crop maturity, as a result of saline water irrigation the soil infiltration was reduced by an average of 7.0%. The EC and exchangeable sodium percentage (ESP) of the experimental plots were increased by 2.2 dS m −1 and 9.0, respectively. The average yield of barley and mustard was 264 and 177 kg ha −1 respectively. It was concluded that production of barley and mustard crops could be increased further by better levelling the plots, reducing level differences to less than 10 cm. The saline water should be used carefully to irrigate fine‐textured soils to keep the salinity within the safe limit to avoid permanent failure of crop growth and yield. Copyright © 2008 John Wiley & Sons, Ltd.

Groundwater and soil salinity variations in a canal command area in Pakistan - Muhammad Latif; Muhammad Zakria Ahmad (Irrigation and Drainage, 2009)
This three‐year study was undertaken to investigate the groundwater and soil salinity variation in a canal‐irrigated area. Water and soil samples were collected along 54 tertiary canals located on six secondary canals (two each at head, middle and tail end) of a main canal. Data of crop yield and income of the farmers were also collected. The results show that electrical conductivity (EC) of groundwater increased from head to lower reaches along all the irrigation channels, i.e. main, the secondary and the tertiary canals. Similarly, the soil water EC e also increased with increased distance from the head of the irrigation system. Reduced canal water supply at lower reaches of the irrigation system forced the downstream water users to pump more groundwater, thereby increasing their irrigation cost. The deteriorating groundwater quality further adds misery to the downstream farmers by degrading productivity of their lands caused by excessive use of saline groundwater. Location of the water users along the canal irrigation system had an impact on their crop yield as well as income and these parameters decreased with increased distance from the head of the irrigation channels. For example, the net income of the tail‐end farmers varied from 43% to 59% of the head‐end farmers. Copyright © 2008 John Wiley & Sons, Ltd.

Estimation of Clark’s Instantaneous Unit Hydrograph Parameters and Development of Direct Surface Runoff Hydrograph - Muhammad Masood Ahmad; Abdul Razzaq Ghumman; Sajjad Ahmad (Water Resources Management, 2009)

Anatomical adaptations to salinity in cogon grass [Imperata cylindrica (L.) Raeuschel] from the Salt Range, Pakistan - Mansoor Hameed; Muhammad Ashraf; Nargis Naz (Plant and Soil, 2009)

Functional analysis of cotton small heat shock protein promoter region in response to abiotic stresses in tobacco using Agrobacterium-mediated transient assay - Muzna Zahur; Asma Maqbool; Muhammad Irfan; Muhammad Younas Khan Barozai; Uzma Qaiser; Bushra Rashid; Tayyab Husnain; Shiekh Riazuddin (Molecular Biology Reports, 2009)

Neurotoxic and cardiotoxic effects of cocaine and ethanol - Muhammad U. Farooq; Archit Bhatt; Mehul B. Patel (Journal of Medical Toxicology, 2009)

Housekeeping gene stability in pristane-induced arthritis and antigen-induced pulmonary inflammation of rats - Congshan Jiang; Liesu Meng; Wenhua Zhu; Muhammad Shahzad; Xudong Yang; Shemin Lu (Inflammation Research, 2009)

In Vitro Distribution of Gold in Serum Proteins after Incubation of Sodium Aurothiomalate and Auranofin with Human Blood and its Pharmacological Significance - Mohammad S. Iqbal; Syed G. Taqi; Muhammad Arif; Muhammad Wasim; Muhammad Sher (Biological Trace Element Research, 2009)

Coexistence of arbuscular mycorrhizae and dark septate endophytic fungi in an undisturbed and a disturbed site of an arid ecosystem - Muhammad S. Chaudhry; Syed U. Rahman; Muhammad S. Ismaiel; Ghulam Sarwar; Bushra Saeed; Faiz-ul-Hassan Nasim (Symbiosis, 2009)

Investigating the concurrent presence of HCV in serum, oral fluid and urine samples from chronic HCV patients in Faisalabad, Pakistan - Muhammad Shafique; Nasir Ahmad; Fazli R. Awan; Tanveer Mustafa; Mujib Ullah; Javed A. Qureshi (Archives of Virology, 2009)

Activation of extracellular signal-regulated kinase in MDBK cells infected with bovine viral diarrhea virus - Daisuke Yamane; Muhammad Atif Zahoor; Yassir Mahgoub Mohamed; Walid Azab; Kentaro Kato; Yukinobu Tohya; Hiroomi Akashi (Archives of Virology, 2009)

Exogenously applied polyamines increase drought tolerance of rice by improving leaf water status, photosynthesis and membrane properties - Muhammad Farooq; Abdul Wahid; Dong-Jin Lee (Acta Physiologiae Plantarum, 2009)

Antifungal activity of methanol and n -hexane extracts of three Chenopodium species against Macrophomina phaseolina - Arshad Javaid; Muhammad Amin (Natural Product Research, 2009)

Predatory potential of three hunting spiders inhabiting the rice ecosystems - Hafiz Muhammad Tahir; Abida Butt (Journal of Pest Science, 2009)

Insoluble but enzymatically active α-amylase from Bacillus licheniformis - Naeem Rashid; Alia Farooq; Ikram-ul-Haq; Muhammad Akhtar (Biologia, 2009)

Programmed Cell Death Pathways and Current Antitumor Targets - Mei Lan Tan; Jer Ping Ooi; Nawfal Ismail; Ahmed Ismail Hassan Moad; Tengku Sifzizul Tengku Muhammad (Pharmaceutical Research, 2009)

Prevalence of hepatitis C virus (HCV) genotypes in Balochistan - Sarwat Afridi; Muhammad Naeem; Abid Hussain; Naseebullah Kakar; Masroor Ellahi Babar; Jamil Ahmad (Molecular Biology Reports, 2009)

Botanical origin of Indian celery seed (fruit) - Takuro Maruyama; Ahmed Abbaskhan; Muhammad Iqbal Choudhary; Yoshisuke Tsuda; Yukihiro Goda; Michel Farille; Jean-Pierre Reduron (Journal of Natural Medicines, 2009)

Determination of toxic elements in different brands of cigarette by atomic absorption spectrometry using ultrasonic assisted acid digestion - Tasneem Gul Kazi; Nusrat Jalbani; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Abdul Qadir Shah (Environmental Monitoring and Assessment, 2009)

Angepasste wasserfördertechnologie unter einsatz von pumpen im turbinenbetrieb - Peter Oberle; Muhammad Ikhwan; Franz Nestmann; Jochen Fritz; Thillainatarajan Ravisundar (WASSERWIRTSCHAFT, 2009)

Bewirtschaftung unterirdischer Fließgewässer in Karstgebieten —Pilotstudie auf Java, Indonesien - Franz Nestmann; Peter Oberle; Muhammad Ikhwan; Tobias Lux; Ulrich Scholz (WASSERWIRTSCHAFT, 2009)

An estimation of the height system bias parameter N 0 using least squares collocation from observed gravity and GPS-levelling data - Muhammad Sadiq; Carl C. Tscherning; Zulfiqar Ahmad (Studia Geophysica et Geodaetica, 2009)

In vitro plantlet regeneration of “dwarf” Indian olive (Elaeocarpus robustus Roxb.): a fruit plant of Bangladesh - Md. Mahabubur Rahman; Muhammad Nurul Amin; Futoshi Ishiguri; Shinso Yokota; Rubaiyat Sharmin Sultana; Yuya Takashima; Kazuya Iizuka; Nobuo Yoshizawa (Plant Biotechnology Reports, 2009)

Performance assessment of irrigation management transfer from government‐managed to farmer‐managed irrigation system: a case study - Muhammad Latif; Javaid A. Tariq (Irrigation and Drainage, 2009)
The government of NWFP, Pakistan, established an autonomous body, the Frontier Irrigation and Drainage Authority (FIDA), in 1997 to effectively cope with the emerging challenges in irrigation management. Six distributaries were recently transferred to farmers' organizations under the irrigation management transfer (IMT) for their operation and management. Results of the study revealed that the irrigation supplies are adequate to meet the crop water requirements. The relative water supply (RWS) index varies from 1.66 to 2.02 during summer, whereas in winter it varies from 2.22 to 2.55. The delivery performance ratio (DPR) during summer varies from 0.78 to 0.83 and in winter from 0.73 to 0.63. Irrigation supplies were reliable during both summer and winter seasons. Due to improved irrigation supply, annual irrigation intensity has increased by 25%. There is a prominent increase in yield of maize (40%), sugarcane (55%) and wheat (43%). The irrigation service fee collected was approximately 60% of the fee assessed. Hydraulic committees at each distributary should be established to operate the distributary according to crop demand. Awareness of the farmers should be created regarding the farm irrigation application methods to avoid over‐irrigation and wastage of water. Copyright © 2008 John Wiley & Sons, Ltd.

Garlic: Nature's Protection Against Physiological Threats - Masood Sadiq Butt; Muhammad Tauseef Sultan; Mehmood S. Butt; Javaid Iqbal (Critical Reviews in Food Science and Nutrition, 2009)

Methyl jasmonate alleviated salinity stress in soybean - Ji Young Yoon; Muhammad Hamayun; Su-Kyung Lee; In-Jung Lee (Journal of Crop Science and Biotechnology, 2009)

Upscaling of the permeability by multiscale wavelet transformations and simulation of multiphase flows in heterogeneous porous media - M. Reza Rasaei; Muhammad Sahimi (Computational Geosciences, 2009)

Feed forward neural network and interpolation function models to predict the soil and subsurface sediments distribution in Bam, Iran - Khalil Rezaei; Bernard Guest; Anke Friedrich; Farajollah Fayazi; Muhammad Nakhaei; Ali Beitollahi; Seyed Mahmoud Fatemi Aghda (Acta Geophysica, 2009)

Green Tea: Nature's Defense against Malignancies - Masood Sadiq Butt; Muhammad Tauseef Sultan (Critical Reviews in Food Science and Nutrition, 2009)

Gibberellin production and plant growth promotion by a newly isolated strain of Gliomastix murorum - Sumera Afzal Khan; Muhammad Hamayun; Ho-Youn Kim; Hyeok-Jun Yoon; In-Jung Lee; Jong-Guk Kim (World Journal of Microbiology and Biotechnology, 2009)

Concentration dependent growth/non-growth linked kinetics of endosulfan biodegradation by Pseudomonas aeruginosa - Sarfraz Hussain; Muhammad Arshad; Baby Shaharoona; Muhammad Saleem; Azeem Khalid (World Journal of Microbiology and Biotechnology, 2009)

Ectodermal dysplasia-cutaneous syndactyly syndrome maps to chromosome 7p21.1-p14.3 - Muhammad Tariq; Muhammad Nasim Khan; Wasim Ahmad (Human Genetics, 2009)

Future change in the frequency of warm and cold spells over Pakistan simulated by the PRECIS regional climate model - Siraj ul Islam; Nadia Rehman; Muhammad Munir Sheikh (Climatic Change, 2009)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)

Evaluation of the Acute Toxicity of Profenofos and Its Effects on the Behavioral Pattern of Fingerling Common Carp (Cyprinus carpio L., 1758) - Muhammad Ismail; Rahat Ali; Tayyaba Ali; Usman Waheed; Qaiser Mahmood Khan (Bulletin of Environmental Contamination and Toxicology, 2009)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for improving growth and yield of wheat (Triticum aestivum L.) under salt-stressed conditions - Zahir Ahmad Zahir; Usman Ghani; Muhammad Naveed; Sajid Mahmood Nadeem; Hafiz Naeem Asghar (Archives of Microbiology, 2009)

Sources of Arsenic and Fluoride in Highly Contaminated Soils Causing Groundwater Contamination in Punjab, Pakistan - Abida Farooqi; Harue Masuda; Rehan Siddiqui; Muhammad Naseem (Archives of Environmental Contamination and Toxicology, 2009)

Microbial transformation of 18β-glycyrrhetinic acid by Cunninghamella elegans and Fusarium lini , and lipoxygenase inhibitory activity of transformed products - Muhammad Iqbal Choudhary; Zafar Ali Siddiqui; Sarfraz Ahmed Nawaz; Atta-ur-Rahman (Natural Product Research, 2009)

Cladosporium sphaerospermum as a new plant growth-promoting endophyte from the roots of Glycine max (L.) Merr. - Muhammad Hamayun; Sumera Afzal Khan; Nadeem Ahmad; Dong-Sheng Tang; Sang-Mo Kang; Chae-In Na; Eun-Young Sohn; Young-Hyun Hwang; Dong-Hyun Shin; Byung-Hyun Lee; Jong-Guk Kim; In-Jung Lee (World Journal of Microbiology and Biotechnology, 2009)

Expression and characterization of Trichoderma virens UKM-1 endochitinase in Escherichia coli - Nadiawati Alias; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Farah Diba Abu Bakar; Nik Azmi Nik Mahmood; Rosli Md Illias (World Journal of Microbiology and Biotechnology, 2009)

Epidermal growth factor receptors: function modulation by phosphorylation and glycosylation interplay - Afshan Kaleem; Ishtiaq Ahmad; Daniel C. Hoessli; Evelyne Walker-Nasir; Muhammad Saleem; Abdul Rauf Shakoori; Nasir-ud-Din (Molecular Biology Reports, 2009)

A simple method for simultaneous determination of some organic liquids in in-process materials and effluents produced in the manufacture of amoxicillin and ampicillin - Mohammad S Iqbal; Muhammad A Akmal (Environmental Monitoring and Assessment, 2009)

High mortality and sex ratio imbalance in a critically declining Oriental White-backed Vulture population (Gyps bengalensis) in Pakistan - Muhammad Arshad; Muhammad J. I. Chaudhary; Michael Wink (Journal of Ornithology, 2009)

Phylogeny and phylogeography of critically endangered Gyps species based on nuclear and mitochondrial markers - Muhammad Arshad; Javier Gonzalez; Abdel Aziz El-Sayed; Tim Osborne; Michael Wink (Journal of Ornithology, 2009)

Mating system and seed variation of Acacia hybrid (A. mangium × A. auriculiformis) - Chin-Hong Ng; Soon-Leong Lee; Kevin Kit-Siong Ng; Norwati Muhammad; Wickneswari Ratnam (Journal of Genetics, 2009)

Evolutionary history of the somatostatin and somatostatin receptors - Muhammad Moaeen-Ud-Din; Li Guo Yang (Journal of Genetics, 2009)

Iron content variations in sphalerite and their effects on reflectance and internal reflections under reflected light - Salih Muhammad Awadh (Arabian Journal of Geosciences, 2009)

Streamline pattern and salt leaching through progressive flooding between subsurface drains - Muhammad Saffar Mirjat; Derek A. Rose (Irrigation and Drainage, 2009)
This paper examines an efficient method of removing salts through progressive flooding of surface strips between subsurface drains. The method has been tested in the laboratory using a sand tank model experiment. The work extends earlier theoretical investigations by Youngs and Leeds‐Harrison ( 2000 ) which suggest that more uniform leaching with less water can be obtained by constraining the infiltrating area with the use of bunds, initially flooding only the region midway between the drains and then progressively increasing the flooded area towards the drains until the whole area between the drains is flooded. Streamlines were traced to determine flow pattern and solute movement under complete and partial flooding. The tracing results suggest that partial flooding is more effective than complete flooding as the streamlines move faster and require less time to carry the salt towards the drain. The results have been further supported by the pore volumes of solute and salt loads leached under partial and complete flooding. The quarter flooding situation was extremely efficient followed by half and three‐quarter situations where solute leaching towards drains was higher than complete flooding. Results show that 59% superfluous good quality water is required to desalinise the area midway between drains with complete flooding, as compared to quarter area of flooding. Similarly, half and three‐quarter flooding situations require 21 and 37% additional good quality water, respectively, to leach the same amount of salts from the area midway between drains. Copyright © 2008 John Wiley & Sons, Ltd.

Leishmanicidal potential of N-substituted morpholine derivatives: Synthesis and structure–activity relationships - Khalid Mohammed Khan; Muhammad Zarrar Khan; Muhammad Taha; Ghulam Murtaza Maharvi; Zafar Saeed Saify; Shahnaz Parveen; Muhammad Iqbal Choudhary (Natural Product Research, 2009)

A convenient synthesis of p -substituted 1-arylsulfonyl-pyrrolidin-2-ones - Muhammad Zareef; Rashid Iqbal; Khalid M. Khan; Javid H. Zaidi; Zia-Ullah; Muhammad Arfan (Natural Product Research, 2009)

Elaeagnoside, chymotrypsin inhibiting steroidal glucoside from Elaeagnus orientalis - Muhammad Ayaz; Muhammad Riaz; Abdul Malik; Ejaz Ahmad; Itrat Fatima; Muhammad Arif Lodhi; Muhammad Iqbal Chaudhary (Natural Product Research, 2009)

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties - Syed Ali Imran Bokhari; Farooq Latif; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2009)

Comparative efficacy of standard AGID and precipitinogen inhibition test with monoclonal antibodies based competitive ELISA for the serology of Peste des Petits Ruminants in sheep and goats - Muhammad Munir; Muhammad Siddique; Qurban Ali (Tropical Animal Health and Production, 2009)

Methionine+cystine requirement of broiler chickens fed low-density diets under tropical conditions - Usama Aftab; Muhammad Ashraf (Tropical Animal Health and Production, 2009)

Enhancing the performance of transplanted coarse rice by seed priming - Muhammad Farooq; Shahzad M. A. Basra; N. Ahmad; G. Murtaza (Paddy and Water Environment, 2009)

Stability of Vitamins during Extrusion - Mian N. Riaz; Muhammad Asif; Rashida Ali (Critical Reviews in Food Science and Nutrition, 2009)

Solid-state fermentation-supported enhanced production of α-galactosidase by a deoxyglucose-resistant mutant of Aspergillus niger and thermostabilization of the production process - Muhammad Ibrahim Rajoka; Muhammad Siddique Awan; Mahjabeen Saleem; Najma Ayub (World Journal of Microbiology and Biotechnology, 2009)

Removal of Nickel onto Alkali Treated Rice Bran - Muhammad Nadeem Zafar; Imran Abbas; Raziya Nadeem; Munir Ahmad Sheikh; Muhammad Afzal Ghauri (Water, Air, & Soil Pollution, 2009)

Nutrient content of tropical edible seaweeds, Eucheuma cottonii, Caulerpa lentillifera and Sargassum polycystum - Patricia Matanjun; Suhaila Mohamed; Noordin M. Mustapha; Kharidah Muhammad (Journal of Applied Phycology, 2009)

Relationships among different geographical groups, agro-morphology, fatty acid composition and RAPD marker diversity in Safflower (Carthamus tinctorius) - Muhammad A. Khan; Sabine von Witzke-Ehbrecht; Brigitte L. Maass; Heiko C. Becker (Genetic Resources and Crop Evolution, 2009)

A new strain of Arthrinium phaeospermum isolated from Carex kobomugi Ohwi is capable of gibberellin production - Sumera Afzal Khan; Muhammad Hamayun; Ho-youn Kim; Hyeok-jun Yoon; Jong-cheol Seo; Yeon-sik Choo; In-jung Lee; Sang-dal Kim; In-koo Rhee; Jong-guk Kim (Biotechnology Letters, 2009)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

Computational Model Provides Insight into the Distinct Responses of Neurons to Chemical and Topographical Cues - Leandro Forciniti; Christine E. Schmidt; Muhammad H. Zaman (Annals of Biomedical Engineering, 2009)

Facile, economical and direct synthesis of 9-anilinoacridines - Khalid M. Khan; Nosheen A. Rao; Zia-Ullah; Muhammad Ali; Shahnaz Perveen; Muhammad Iqbal Choudhary; Atta-Ur-Rahman; Wolfgang Voelter (Natural Product Research, 2009)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)